THE WOMAN’S EXISTENCE IN WALTER TEVIS’S THE QUEEN’S GAMBIT - Rima Sarah; Tenny Sudjatnika; Agry Pramita (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2023)
This study examines the existence of women from the main character in novel using the feminism theory from Simone de Beauvoir. This study aims to identify the depiction of the main character and analyze the existence of women in the novel The Queen's Gambit by Walter Tevis. The data used is documentation using note-taking techniques and content analysis. The results of this study: (1) Women's representation in chess was often underestimated in the 1950-1960s era. (2) Discrimination against women cannot be avoided so that they do not get equal opportunities in the world of sports. (3) Beth, as the main character, is one of the pioneers in rejecting discriminatory treatment in sports, especially chess. (4) The main character describes women's existence through tenacity, belief, intelligence, attitude, and expressions of their defense. This research suggests that the existence of women can be fought for in sports, especially chess.